A New High Hydrostatic Pressure Process to Assure the Microbial Safety of Human Milk While Preserving the Biological Activity of Its Main Components - Demazeau, Gérard; Plumecocq, Adrien; Lehours, Philippe; Martin, Patrice; Couëdelo, Leslie; Billeaud, Claude (Frontiers in Public Health, 2018)
Abstract Background: The main process used to pasteurize human milk is the low-temperature, long-time Holder method. More recently, the high-temperature, short-time method has been investigated. Both processes lead to the appropriate inactivation of vegetative bacterial forms but are ineffective against bacterial spores. Research Aims/Questions: We aimed to accomplish two main objectives: inactivation of all pathogens, including spores; and preservation of the activity of milk components. Design/Methods: Recently, a novel high-hydrostatic pressure process has been developed by HPBioTECH. Using the same raw human milk samples, we compared the effects of this method with those of the Holder method on vegetative and spore spores). Use of the high-hydrostatic pressure process led to microbial decontamination of 6 log for both S. aureus and B. cereus. Additionally, the bioactivity of the main components of human milk was preserved, with activities of lipase, α-lactalbumin, casein, lysozyme, lactoferrin, and sIgA of approximately 80%, 96-99%, 98-100%, 95-100%, 93-97%, and 63-64%, respectively.